The genesis of state policy in the field of education in Ukraine during the period of independence - Savenko, Viktor; Ignatenko, Nataliia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The peculiarities of the implementation of state policy in the field of education in Ukraine during the period of independence (199˗2020) and its relationship with the field of legislation are characterized; the main directions of implementation of educational policy at different stages of development of the state are analyzed. State policy in the field of education is seen as a set of theoretical ideas, goals, objectives and practical measures aimed at developing education and ensuring a stable course of the government and its subordinates to improve the welfare of people, education of conscious citizens, national interests, strengthening the country’s authority and competitiveness in the international arena.